Extracellular vesicles from mice with alcoholic liver disease carry a distinct protein cargo and induce macrophage activation through heat shock protein 90. Issue 5 (6th April 2018) - Saha, Banishree; Momen‐Heravi, Fatemeh; Furi, Istvan; Kodys, Karen; Catalano, Donna; Gangopadhyay, Anwesha; Haraszti, Reka; Satishchandran, Abhishek; Iracheta‐Vellve, Arvin; Adejumo, Adeyinka; Shaffer, Scott A.; Szabo, Gyongyi
Abstract : A salient feature of alcoholic liver disease (ALD) is Kupffer cell (KC) activation and recruitment of inflammatory monocytes and macrophages (MØs). These key cellular events of ALD pathogenesis may be mediated by extracellular vesicles (EVs). EVs transfer biomaterials, including proteins and microRNAs, and have recently emerged as important effectors of intercellular communication. We hypothesized that circulating EVs from mice with ALD have a protein cargo characteristic of the disease and mediate biological effects by activating immune cells. The total number of circulating EVs was increased in mice with ALD compared to pair‐fed controls. Mass spectrometric analysis of circulating EVs revealed a distinct signature for proteins involved in inflammatory responses, cellular development, and cellular movement between ALD EVs and control EVs. We also identified uniquely important proteins in ALD EVs that were not present in control EVs. When ALD EVs were injected intravenously into alcohol‐naive mice, we found evidence of uptake of ALD EVs in recipient livers in hepatocytes and MØs. Hepatocytes isolated from mice after transfer of ALD EVs, but not control EVs, showed increased monocyte chemoattractant protein 1 mRNA and protein expression, suggesting a biological effect of ALD EVs. Compared to control EV recipient mice, ALD EV recipient mice had increased numbers of F4/80 hi cluster of differentiation 11b (CD11b) lo KCs and increased percentages of tumor necrosis factor alpha–positive/interleukin 12/23–positive (inflammatory/M1) KCs and infiltrating monocytes (F4/80 int CD11b hi ), while the percentage of CD206 + CD163 + (anti‐inflammatory/M2) KCs was decreased. In vitro, ALD EVs increased tumor necrosis factor alpha and interleukin‐1β production in MØs and reduced CD163 and CD206 expression. We identified heat shock protein 90 in ALD EVs as the mediator of ALD‐EV‐induced MØ activation. Conclusion: Our study indicates a specific protein signature of ALD EVs and demonstrates a functional role of circulating EVs containing heat shock protein 90 in mediating KC/MØ activation in the liver. (Hepatology 2018;67:1986‐2000).